Pengaruh Problem Based Learning Berbantuan Animasi AI Terhadap Hasil Belajar Matematika SD 1 Lukluk Badung - I Gusti Ayu Shinta Tirta Mahoni; Ni Nyoman Mariani; Gusti Ayu Agung Riesa Mahendradhani (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
Mathematics instruction in elementary schools often relies on teacher-centered methods, making abstract mathematical concepts exceedingly difficult for young students to grasp. This study aims to determine the significant effect of implementing the Problem-Based Learning (PBL) model assisted by Artificial Intelligence (AI) animated videos on the mathematics learning outcomes of third-grade students. This quantitative experimental study employed a pre-experimental One-Group Pretest-Posttest Design, involving a total sample of 30 third-grade students measured through a validated cognitive domain achievement test. The results demonstrated a highly significant improvement in students' mathematics learning outcomes after receiving the intervention. The pretest mean score was 57.00, which increased substantially to 82.33 in the posttest, yielding a mean difference of 25.33. Furthermore, data analysis using the Paired Sample t-Test revealed a significance value of less than 0.001 (t = -8.490, df = 29). Consequently, the null hypothesis was firmly rejected, indicating a substantial and meaningful enhancement in student comprehension regarding length measurement concepts. In conclusion, integrating the PBL model with AI-generated animated videos serves as a highly effective pedagogical strategy that significantly improves mathematics learning outcomes in elementary education. Keywords: Problem Based Learning, AI Animated Video, Learning Outcomes, Mathematics Education.